THE RUS IS POWERFUL, SHARP-EYED, SOMETHING OF HIMSELF THE DEVELOPMENT OF RUSSIAN AND NORTH CAUCASIAN COOPERATION - Y. Klychnikov (Гуманитарные и юридические исследования)
The work reconstructs the events of the early stage of the formation of Russian-North Caucasian relations. The circumstances of the appearance of Russians in the region, caused by the need to establish trade contacts with the East, are shown. The role of the Khazar Khaganate in ensuring regular contacts between the Eastern Slavs and the tribes of the Northern Caucasus is under consideration. The reasons that led to the clashes between the emerging Kievan Rus and Khazaria are analyzed. The ambiguity of the first contacts between the Russian troops and the autochthonous population is demonstrated. The foreign policy of Prince Svyatoslav, who prioritized the southern direction, is estimated. His campaigns in the Caucasus led to the collapse of the geopolitical rival and created the conditions for the emergence of the Russian fort post, which subsequently took shape in the Tmutarakan principality. Svyatoslav's successes were fixed during the reign of Prince Vladimir I. He actively contacted with the inhabitants of Tmutarakan, and, apparently, during his ruling not only the Russian administration appeared in the region, but also Eastern Slavic settlers began to take root. Using Tmutarakan, Russia could pursue an active policy in the Crimea, strengthen its influence on the peoples of the North Caucasus. This allowed forming a long-term historical partnership, which is understood as cooperation-rivalry and is designated by the term "cooperation".